2008
DOI: 10.1016/j.ijgo.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human mesenchymal stem cells from third‐trimester amniotic fluid

Abstract: Multipotent MSCs can be obtained from AF in the third trimester, which may be less dangerous than the second trimester to women and their fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 8 publications
(7 reference statements)
2
49
0
2
Order By: Relevance
“…In addition, these amniotic fluid stem (AFS) cells were not tumorigenic, retained long telomeres, and maintained a normal karyotype for over 250 population doublings (De Coppi et al, 2007). The presence of NANOG protein and SSEA-4 in human AFS cells (Roubelakis et al, 2007), their differentiation into chondrocytes (Kim et al, 2007;Kolambkar et al, 2007) and osteocytes (You et al, 2008), and the presence of telomerase activity (Kim et al, 2007) have been reported. It seems therefore that AFS cells are pluripotent stem cells similar to -but less differentiated -than BM-MSCs (Kim et al, 2007).…”
Section: Amniotic Fluid Derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these amniotic fluid stem (AFS) cells were not tumorigenic, retained long telomeres, and maintained a normal karyotype for over 250 population doublings (De Coppi et al, 2007). The presence of NANOG protein and SSEA-4 in human AFS cells (Roubelakis et al, 2007), their differentiation into chondrocytes (Kim et al, 2007;Kolambkar et al, 2007) and osteocytes (You et al, 2008), and the presence of telomerase activity (Kim et al, 2007) have been reported. It seems therefore that AFS cells are pluripotent stem cells similar to -but less differentiated -than BM-MSCs (Kim et al, 2007).…”
Section: Amniotic Fluid Derived Cellsmentioning
confidence: 99%
“…AFCs can be collected during the second trimester of gestation by amniocentesis. Amniotic fluid is rich in mesenchymal stem cells (Fauza, 2004;Siegel et al, 2008) that possess high proliferation potential, are OCT4 positive; and are able to differentiate into cells types of the three germ layers, like adipogenic, osteogenic, myogenic and endothelial cell types, neurogenic cell types, and hepatic cell types (De Coppi et al, 2007;You et al, 2008;Zheng et al, 2008). A recent study reported that c-Kit+ Lin-cells derived from human amniotic fluid displayed a multilineage differentiation potential in vitro to the haematopoietic lineages (Ditadi et al, 2009).…”
Section: Amniotic Fluid Derived Cellsmentioning
confidence: 99%
“…However, due to their adipogenic, osteogenic, myogenic, endothelial, neurogenic, hepatic, chondrogenic and renal differentiation potency (Tsai et al 2004, AFMSCs may be a readily available source similar to ESCs for large numbers of different cells progenitors (De Coppi et al 2007). In addition, AFMSCs have not shown tumorigenicity, thus making them an exciting new source of regenerative cells (You et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, characteristics of MSCs are the absence of expression of typical hematopoietic antigens like CD34 and CD45, and the expression of surface markers like Stro-1, CD44, CD73, CD90, CD105 and CD166 (Pittenger et al, 1999). Human MSCs, which are probably responsible for normal tissue renewal, as well as for response to injury (Tsai et al, 2007), have been isolated from several tissues, including bone marrow (Kastrinaki et al, 2008;Yoo et al, 1998), periosteum (Nakahara et al, 1990), perichondrium (Dounchis et al, 1997) (You et al, 2008;Steigman & Fauza, 2007;Fauza, 2004), placenta (Barlow et al, 2008, Steigman & Fauza, 2007Fauza, 2004: Matikainen & Laine, 2005, amniotic membrane (Díaz-Prado et al, 2010a& 2010bAlviano et al, 2007), umbilical cord (Baksh et al, 2007 and umbilical cord blood (Mareschi et al, 2001). Although bone marrow is the usual source of MSCs, umbilical cord blood is emerging as an important reservoir for stem cells capable of differentiation into many cell types and possessing the advantages of immune status and relatively unshortened telomere length (McGuckin et al, 2005).…”
Section: Mesenchymal Stem Cells Transplantationmentioning
confidence: 99%